FUNDRAISING MANAGEMENT OF MONEY WAQF IN INDONESIAN WAQF SAVINGS IN A SHARIA REVIEW - Amrin, Amrin; Rahim, Abd; Yono, Yono (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
This study aims to examine the fundraising management of money waqf in Indonesian waqf savings from a sharia perspective. This research uses a type of qualitative research with field studies on Indonesian Wakaf Savings Dompet Dhuafa Republika in Ciputat Indah Permai with an approach descriptive analysis. The data collection techniques are interviews, documentation and observation. As for data analysis using data reduction, Arranging categories and Synthesizing in inductive analysis. The research results show that professionalism, transparency and accountability in the management of TWI cash waqf are by sharia in the formation of nazir institutions, waqf asset management activities, investment in banking, portfolio and investment in the real sector as well as an annual report. So steps are needed to maintain Nazir's level of professionalism, it is time for Nazir to make an annual report every year and it is known to the public that TWI should collaborate with other foundations to collect, maximize and distribute waqf benefits.